Productivity enhancement of stepped solar still integrated MEMS light sensors for solar tracker - Ali. F. Muftah (The Journal of Engineering and Exact Sciences)
Water is life, and the threat of unsustainable means of potable water supplies has led to the reviews of various renewable energy sources to create a cleaner and more efficient solution for potable water supply. The aim of this study is to present a way in which the efficiency of stepped solar still can be increased. It is to increase the efficiency of solar still by increasing the amount of time that the solar still is directly perpendicular to the sunlight. The Micro-Electro-Mechanical Systems (MEMS) light sensors for solar tracking are used to enhance the productivity. The results obtained indicate that the use of MEMS light sensors for solar tracking are used to makes a solar still to be predictable and it equally increases its efficiency in terms of distillate yield and overall performance.